Acceptance of national wind power development and exposure: A case-control choice experiment approach - Anders Dugstad; Kristine M. Grimsrud; Gorm Kipperberg; Henrik Lindhjem; Ståle Navrud (Statistics Norway, Research Department, 2020)
Despite a large stated-preference literature on wind power externalities, few SP studies employ a case-control approach to examine whether people's acceptance of new wind power developments increases or decreases with exposure to and familiarity with wind turbines. Furthermore, the existing studies are inconclusive on this issue. In a case-control discrete choice experiment we measure the level of acceptance in terms of people's willingness-to-accept compensation for having future landbased wind power developments in Norway; comparing exposed and non-exposed people's WTA. We find that exposure lowers acceptance. Furthermore, exposed people are also unwilling to pay as much as non-exposed people to increase general domestic renewable energy production (from all sources), and thus have lower acceptance for such renewable energy policy initiatives. After testing for type of exposure, we argue that the inconclusiveness in the literature of how exposure affects acceptance of wind power developments could be due to the fact that impacts considered differs somewhat across studies.
Keywords: Q48; Q51; Q57; 330; Discrete Choice Experiment; exposure; wind power; willingness-to-accept; societal acceptance; familiarity